Analisis Perbandingan Proses Pengolahan Citra Menggunakan FPGA dan Mikrokomputer - Muhammad Naufal; Wijaya Kurniawan; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Image processing is an important aspect in life because human needs are increasingly growing day by day, so we need a system that can process image effectively. To find out what systems can effectively process images, a comparison analysis of image processing between two systems, FPGA and Microcomputer is performed. FPGA used is myRIO while the Microcomputer used is Raspberry Pi. The study was conducted with common image processing algorithms such as Gaussian blur, Laplacian edge and Sobel edge. First the RGB image is converted to grayscale for easy image processing and then eliminated its noisenya with gaussian blur algorithm. After that the image is detected edge with laplacian edge and sobel edge algorithms. The test was performed by processing three different image sizes on three different algorithms and performed ten tests and taken the average time of image processing on both systems. The mean time of image processing with Gaussian blur algorithm is 0.485s on FPGA and 0.165s on Microcomputer. For Laplacian edge mean time algorithm is 0.492s on FPGA and 0.202s on Microcomputer while for Sobel edge algorithm its average time is 0.498s on FPGA and 0.234s on Microcomputer. But actually for all algorithms, FPGA time remains the same but different on three different sized images respectively are 0.01053, 0.03074 and 0.06076 seconds.